HDAC11 is a novel regulator of fatty acid oxidative metabolism in skeletal muscle. (14th July 2020) - Hurtado, Erica; Núñez‐Álvarez, Yaiza; Muñoz, Mar; Gutiérrez‐Caballero, Cristina; Casas, Josefina; Pendás, Alberto M.; Peinado, Miguel A.; Suelves, Mònica
Abstract : Skeletal muscle is the largest tissue in mammalian organisms and is a key determinant of basal metabolic rate and whole‐body energy metabolism. Histone deacetylase 11 (HDAC11) is the only member of the class IV subfamily of HDACs, and it is highly expressed in skeletal muscle, but its role in skeletal muscle physiology has never been investigated. Here, we describe for the first time the consequences of HDAC11 genetic deficiency in skeletal muscle, which results in the improvement of muscle function enhancing fatigue resistance and muscle strength. Loss of HDAC11 had no obvious impact on skeletal muscle structure but increased the number of oxidative myofibers by promoting a glycolytic‐to‐oxidative muscle fiber switch. Unexpectedly, HDAC11 was localized in muscle mitochondria and its deficiency enhanced mitochondrial content. In particular, we showed that HDAC11 depletion increased mitochondrial fatty acid β‐oxidation through activating the AMP‐activated protein kinase‐acetyl‐CoA carboxylase pathway and reducing acylcarnitine levels in vivo, thus providing a mechanistic explanation for the improved muscle strength and fatigue resistance. Overall, our data reveal a unique role of HDAC11 in the maintenance of muscle fiber‐type balance and the mitochondrial lipid oxidation. These findings shed light on the mechanisms governing muscle metabolism and may have implications for chronic muscle metabolic disease management. Abstract : Schematic representation of histone deacetylase 11 (HDAC11) functions in skeletal muscle tissue. HDAC11 is required for balancing fiber‐type composition and for modulating mitochondrial lipid oxidation in skeletal muscle. Lack of HDAC11 results in enhanced oxidative capacity of muscle tissue, increasing mitochondrial fatty acid β‐oxidation capacity. The functional consequences of HDAC11 deficiency are the improvement of muscle strength and fatigue resistance, indicating a better skeletal muscle performance.